Actividades lúdicas en el desarrollo de la empatía en niños de primer año de educación básica de la unidad educativa "Verbo Divino", provincia Bolívar, cantón Guaranda, periodo 2024 - Ledesma Hurtado, Kamila Pamela (2025)
Playful activities play a fundamental role in the integral development of children during early childhood, as they offer multiple benefits ranging from the strengthening of cognitive processes to body awareness, balance control, and improved motor coordination. In this context, the objective of the present research is to determine the role of playful activities as a key factor in the development of empathy in first-year primary school students at Unidad Educativa Verbo Divino, from September to December 2024. This research project follows a mixed-methods approach that combines bibliographic-documentary, field, and descriptive research. We conducted a survey with three teachers of first-year primary education and used an observation sheet to assess 75 children at the same educational level. The results obtained demonstrate that playful activities significantly contribute to the development of empathy in early childhood. The surveys revealed an increase in the ability to understand and express emotions, while the observations highlighted improvements in social interaction, cooperation, and conflict resolution. Furthermore, the findings show that games promote a positive learning environment and stimulate both cognitive and emotional skills. When considered as a whole, the data confirms that playful dynamics play a key role in strengthening students’ development. The research culminated in the development of an educational guide containing ten empathy-focused activities derived from the study’s results